Studi Potensi Pemanfaatan Bunga Telang (Clitoria ternatea L.) Sebagai Media Pembelajaran Sains Untuk Anak Sekolah Dasar - Hasan, Muhammad Nur; Anwar, Thohari (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Acids and bases are basic principles in science, especially chemistry which really needs to be learned for everyone, introducing the principles of acids and bases to children is very important to do so they love science more in the future. Dyes found in nature, especially those derived from plants, when they are in a solution, their color depends on the pH atmosphere, so they can be used as indicators or indicators of acids and bases in solutions. Introducing science from an early age means helping children to start thinking critically and logically. Science helps children experiment, explore and observe their surroundings. This slowly builds children's character to get used to thinking scientifically, is skilled at solving problems, and has high analysis. To introduce science to children, it needs to be packaged in an interesting way, one of which is science magic. To test whether the butterfly pea flower extract has a good pH range, it is first tested in solutions with all pHs from 1 to 14, and the results show that the butterfly pea flower has a good color range, while for scientific magic it is done by making three clear solutions that are not colored, each labeled A, B and C then the solution is given a butterfly pea flower extract and the results show three different colors, solution A is red, solution B is blue and solution C is yellow, in magic the solution A contains an acidic solution, solution B contains plain water and solution C contains an alkaline solution. The results of this study indicate that the quality of science learning media which is the magic game using butterfly pea flowers has the potential to be used as a medium for introducing science at the elementary school level. The conclusion from this study is that it is necessary to design the development of science learning media in the form of magic games to develop higher quality children's cognition so that they are very suitable for use in learning activities.